THE ANALYSIS OF NEED ISLAMIC LEARNING MODEL TO IMPROVE THE EFFECTIVENESS AND QUALITY OF ISLAMIC RELIGIOUS EDUCATION IN STKIP PGRI WEST SUMATERA - Azwar, A.; Jarudin, J. (Universitas Pendidikan Ganesha, 2017)
The development of various diseases of societies such as alcohol, gambling, and promiscuity, a challenge for the world of education, especially religious investigations that play a role in developing the personality of learners who knowledgeable, faithful and devout and noble. Religious education is asked to create a good curriculum is also required to have a clear learning model and measurable again directed. In the learning model, there has been a clear conceptual framework that describes a systematic procedure in organizing learning experiences to achieve the objectives of learning. Thus lecturers and students will more easily recognize and understand and undergo the process of religious learning because it has been prepared in such a way by religious lecturers. The success of applying the model of learning by religious lecturers can be measured the integration between science, faith and taqwa, and noble character in learners themselves so that they become human beings who maintained in ahsanu taqwim. Once the strategic role of religious education, it has become an urgent thing done the development of learning models of religious education in public colleges.